2015
DOI: 10.5424/sjar/2015133-6610
|View full text |Cite
|
Sign up to set email alerts
|

Udder health in organic dairy cattle in Northern Spain

Abstract: This paper presents first data on the udder health status of organic dairy farms in Northern Spain and analyses some management and productive characteristics related to milk production comparing with the conventional sector. Five certified organic farms from the Cantabrian Region were monitored monthly from February 2006 to January 2008 and individual samples of all lactating cows were taken from parturition to the end of lactation. Although organic farms in our study showed a great individual variability, ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 16 publications
2
9
0
Order By: Relevance
“…1). The SCC has been reported to increase significantly with lactation number on organic dairy farms in northern Spain, particularly farms on which antibiotic therapy is not used (Orjales et al, 2016) and has been related to chronic infection after several lactation periods (Villar & López-Alonso, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). The SCC has been reported to increase significantly with lactation number on organic dairy farms in northern Spain, particularly farms on which antibiotic therapy is not used (Orjales et al, 2016) and has been related to chronic infection after several lactation periods (Villar & López-Alonso, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…In fact without hygiene or without an adequate maintenance of milking machine, antibiotic dry therapy and teat dipping are insufficient measures to prevent mammary infections and to achieve low SCC. Recent studies in northern Spain have indicated higher SCC in organically reared herds than in conventionally reared herds (Villar & López-alonso, 2015;Orjales et al, 2016). This is mainly associated with a higher prevalence of chronic subclinical mastitis in organic herds , although the higher SCC may be partly explained by the higher number of parturitions and the lower production rates on organic farms.…”
Section: Introductionmentioning
confidence: 97%
“…In addition to clinical and subclinical udder disease, factors like husbandry, management, genetics, and nutrition and associated metabolic and endocrine changes have some influence on the SCC. In this sense, at a hypothetical identical sanitary condition the lower milk yield and the higher mean age of lactating cows in organic farms compared with conventional farms could leave to a higher SCC in the former (Villar & López-Alonso, 2015). Differences in the udder health between organic and conventional herds are not necessarily only due to a direct effect of the organic management, and many other differences in management routines may exist between organic and conventional farms besides the "purely" organic and such differences might vary across studies (Fall et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Organic farms in Northern Spain have higher SCCs compared with the conventional ones, which could be related to a higher incidence of mastitis (Villar & López-Alonso, 2015). However, it is also well known that other husbandry factors (Schepers et al, 1997) -mainly the higher number of lactations and the lower milk yield observed in the organic farms-could explain at least in part the higher SCC observed in the organic herd.…”
Section: Diagnosis and Intramammary Infection Criteriamentioning
confidence: 97%
“…Overall all the farms were small (<50 cows in lactation) traditional farms, with a high degree of pasture (66-82% dry matter intake (DMI)) and a low milk production (average milk yield: 5950 L) and used homeopathic treatments to some degree. Details of the farms and sampling collection are described in Villar & López-Alonso (2015).…”
Section: Farms and Samplingmentioning
confidence: 99%